RELIGIOUS REASONING ON SOCIAL MEDIA: ULIL ABSHAR ABDALLA AND AHMAD SUAEDY IN INDONESIA’S MINING CONTROVERSY - Zainal Arifin (ILMU USHULUDDIN, 2026)
Abstract: The debate over mining governance in Indonesia has underscored the increasingly prominent role of religious actors in shaping public discussions on extractivism, ecological justice, and development policy. Yet, much of the existing scholarship continues to frame religion primarily as either a source of legitimation or a form of resistance to extractive industries, while the dynamics of religious reasoning within digital public spaces remain relatively underexplored. This study examines how Ulil Abshar Abdalla and Ahmad Suaedy articulate religious reasoning in debates surrounding mining governance during 2024–2025. Drawing on discourse analysis of opinion essays, public statements, and social media posts, the study explores how religious arguments are formulated in response to policy dilemmas, ecological concerns, and inequalities in resource distribution. The findings reveal two distinct modes of religious justification. Ulil develops a pragmatic justification centred on maslahat, moderation, and policy negotiation, whereas Suaedy advances a critical-distributive justification focused on inequality, power relations, and ecological justice. This article proposes the concept of dual justification to explain how religion operates simultaneously as a medium of policy negotiation and as a source of ethical critique within contemporary extractive politics in Indonesia.